SILENCED VOICES, PURSUING JUSTICE: A FEMINIST ETHNOGRAPHY OF CAMPUS SEXUAL VIOLENCE - Nilawaty, Azzah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The efforts of victims of sexual violence (KS) on campus to get justice often clash with the interests of certain parties in maintaining the good name of the campus. In addition, the power relationship between the victim and the perpetrator obstructs the implementation of sanctions on the perpetrator. This study aims to voice the victims of sexual violence on campus in fighting for justice and find out how the survivors deal with the post-sexual violence trauma conditions they experience. The methodology in this research uses a feminist ethnographic approach. There are four main informants who are survivors of KS on campus. Data collection methods through in-depth life history interviews, involved observation, and documentation. The research results show that the culture of ewuh pekewuh is one of the causes of the failure to sanction KS perpetrators. Differences in the perspective of lecturers on campus in seeing KS as a common problem or only personal victims. Campus regulations on the operational standards of implementation (SOP) for the prevention and handling of KS should be the hope of victims to obtain justice. The fact is that it is still not in accordance with what is needed by KS survivors on campus. Keywords: Victims, Sexual Violence, Campus, Survivors, Feminist Ethnography